HISTORICAL STUDY OF CULTURAL STRUCTURE OF CHHATTISGARH: TRADITION, RELIGION, FOLK ART AND CONTEMPORARY CHALLENGES - Patel, Jyotima; Singh, Sanjana (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The cultural heritage of Chhattisgarh is a unique combined heritage of ancient traditions, tribal beliefs, folk arts and temple architecture, which reflects the social diversity of this region. This research systematically reviews the historical development of Chhattisgarh’s cultural heritage, in which religious, social and architectural aspects of ancient and medieval periods have been analyzed. The research has specially highlighted festivals like Hariyali (Harela), Bhojali, traditional arts like Karma dance, wall painting and major cultural places like Sirpur and Malhar. In addition, this study also highlights the contradictions and syncretism between mainstream religion and folk religion, where worship of village deities and religious rituals are deeply embedded in the social structure. The influence of modernity, urbanization, education and digital technology has raised new questions about cultural identity, but at the same time has also created opportunities for innovation for preservation. This research underlines the need for cultural preservation through policy reforms and educational initiatives.